Modern individuality in Hegel's practical philosophy - Rózsa, Erzsébet. (Critical Studies in German Idealism, 2012)
In Modern Individuality in Hegel's Practical Philosophy , Erzsébet Rózsa aims to reconstruct Hegel's theory of individuality in the light of his idea of modernity. Modern individuality is one of the central topics of Hegel's practical philosophy, discussed systematically in the forms of subjectivity in subjective, objective, and practical spirit. Hegel interpreted modern existence and lifeworld in the context of law, politics, economy, and private life. "Infinite subjective freedom" is the historical principle of the "modern age", as well as the basic determination of modern individual forms of existence and knowledge. Modern form of life and mentality based on the values and practical actions of self-knowledge and self-determination is an achievement of historical significance. This radical turn, however, gives a new perspective to the problem of good life: the normative role of substantial values is overshadowed by the stabilizing function of the "objective order" of institutions.